A análise de Alva Noë de um experimento neurocientífico: reflexão acerca da substituição sensorial visual - Vollino, Maurício da Rosa (Universidade do Vale do Rio dos Sinos, 2019)
This dissertation presents Alva Noë’s philosophic analysis about the Paul Bach-y-Rita’s Tactile Visual Substitution System (TVSS), in order to answer the following question: Can a blind person really experience sight when using TVSS? In order to do so, we need to understand the theories that support Noë’s philosophical point of view on visual perception and the importance of TVSS to develop responses on philosophical mental exercises, such as the Molyneux’s question. The TVSS apparatus is a visual prosthetic constituted by a camera, a receiver that converts visual signals to tactile, and an electrode connected to the user’s skin. In current models, the electrode is adapted to the user’s tongue and receives electric signals interpreted by the brain as tactile signals by the sensorimotor cortex. After a period of adaptation, the user perceives the signals as visual. Such an experiment inspired philosophers and psychologists to revisit the Molyneux’s question put to Locke, viz, whether a blind person who perceives objects such as spheres and cubes by touching them would, if their sight were restored, be able to perceive those objects without touching them. While empiricist philosophers such as Locke, Berkeley, and Molyneux, responded negatively to the question, claiming that the blind man needs to have more experience with the new perceptual channel, rationalist philosophers such as Leibniz, Synge, and Lee responded positively since, according to rationalism, a blind would be able to recognize and correctly name objects which they already had the concepts preconceived in their mind. Psychologists such as Morgan, Warren, Strelow used sensory-substitution devices to answer to Molyneux, and their responses agreed with Locke demonstrating that the blind need time to adapt to these devices. Alva Noë, in turn, attributes a positive response to the TVSS due to the sensorimotor contingencies of the user. According to his theory of perception titled the Enact Approach, to perceive it is necessary to act. In this way, it is moving the eyes, approaching sources of sounds or odors that we are able to cognize. The philosopher defends that to sense is to act – it is by using our sensorimotor skills that we are able to perceive. Such a theory is inspired by the Varela et al.’s perceptual theory based in Merleau-Ponty’s phenomenology, which comprises the human being as a being-in-the-world with a embodied perception and involved in the context in which it is inserted. From these characteristics, Noë’s theory therefore assigns a positive answer to the proposed question, since TVSS makes it possible, according to the philosopher, to experience a kind of vision due to the similarities of the tactile perceptual functioning as the human visual is. The Alva Noë’s enact approach, therefore, accepts the functioning of the TVSS as a visual sense, since his theory allows an approximation of the tactile perception provided by the apparatus to the natural vision since both perceptions use sensorimotor knowledge.
Keywords: Abordagem da Enação; Alva Noë; Molyneux; Substituição sensorial; TVSS; Enact approach; Alva Noë; Molyneux; Sensory substitution; TVSS; ACCNPQ::Ciências Humanas::Filosofia